Styx and Scones in the cracked crystal - Cooper, Jay, 1974- (Ready-to-read graphics. Superstar reader!, 2023)
"Styx the cat and Scones the dog live with two friendly witches. When the witches are out, the pets play fetch with their crystal ball. Then it cracks, sprouts legs, and runs off! Can they catch it before the witches get home?"--